Knowledge, attitudes, and practices regarding rabies in Grenada - Glasgow, Lindonne; Worme, Andre; Keku, Emmanuel; Forde, Martin (PLOS Neglected Tropical Diseases, 2019)
Objective While Grenada attained a zero-human-rabies case status since 1970, the authors conducted the first study to assess knowledge, attitudes, and practices that may contribute to this status as well as to receive feedback on the rabies control program in Grenada. Methodology A cross-sectional survey was conducted in July, 2017 with 996 households on the mainland. A questionnaire was administered to collect information on knowledge of rabies and prevention, vaccination practices, perception of institutional responsibilities for rabies control, and evaluation of the anti-rabies program. Results Of the 996 households, 617 (62%) had owners of animals that can be infected with rabies and were included in the analysis. Respondents were very aware of rabies as a disease that can infect animals and humans. The rate of participation in the vaccination program was 51.6% for pets and 38.0% for livestock. About 40% of respondents were knowledgeable about the extent of protection from the rabies vaccine. Respondents did not demonstrate exceptionally high levels of knowledge about animals that were likely to be infected with rabies, neither the anti-rabies programs that were conducted in Grenada. The three most frequent recommendations made to improve the rabies-control programs were: increase education programs, control the mongoose population, and expand the vaccination period each year. Conclusions Conducting a comprehensive national rabies education program, expanding the vaccination program, and increasing the rate of animal vaccination are important steps that need to be taken to maintain the current zero-human-case status.